Non-canonical anchor motif peptides bound to MHC class I induce cellular responses - Lazoura, E.; Lodding, J.; Farrugia, W.; Day, S.; Ramsland, Paul; Apostolopoulos, V. (2009)
The major histocompatibility complex (MHC) on the surface of antigen presenting cells functions to display peptides to the T cell receptor (TCR). Recognition of peptide-MHC by T cells initiates a cascade of signals, which results in the initiation of a T cell dependent immune response. An understanding of how peptides bind to MHC molecules is important for determining the structural basis for T cell dependent immune responses and facilitates the structure-based design of peptides as candidate vaccines to elicit a specific immune response. To date, crystal structures, immunogenicity and in vivo biological relevance have mainly been characterized for high affinity peptide-MHC interactions. From the crystal structures of numerous peptide-MHC complexes it became apparent what canonical sequence features were required for high affinity binding, which led to the ability to predict in most instances peptides with high affinity for MHC. We previously identified the crystal structures of non-canonical peptides in complex with MHC class I (one bound with low affinity and the other with high affinity, but utilizing novel peptide anchors and MHC pockets). It is becoming increasingly evident that other non-canonical peptides can also bind, such as long-, short- and glyco-peptides. However, the in vivo role of non-canonical peptides is not clear and we present here the immunogenicity of two non-canonical peptides and their affinity when bound to MHC class I, H2Kb. Comparison of the three-dimensional structures in complex with MHC suggests major differences in hydrogen bonding patterns with H2Kb, despite sharing similar binding modes, which may account for the differences in affinity and immunogenicity. These studies provide further evidence for the diverse range of peptide ligands that can bind to MHC and be recognized by the TCR, which will facilitate approaches to peptide-based vaccine design. © 2008 Elsevier Ltd. All rights reserved.